Fabrication of perfusable microvessel networks by mimicking in vivo vasculogenesis using a novel scaffold-wrapping method. (March 2023) - Lin, Ying-Ting; Tung, Yen-Ting; Wong, Jhen-Yuan; Wang, Gou-Jen
Graphical abstract: Highlights: A scaffold-wrapping approach for generating a perfusable capillary network with tailored structure was proposed. A cylindrical fibrin scaffold with desired pattern was made by lithography, thermal reflow, PDMS casting, and fibrin afflux. Vasculogenesis resembling scaffold-wrapping was achieved by culturing HUVECs on the surface a cylindrical fibrin scaffold. This customized capillary network with dimensions of micrometer can mimic tissue-specific microvascular characteristics. Abstract: Due to the heterogeneous nature of microvascular structure between organs, it is important to engineer tailored capillary networks that match their physical properties for biochemical/mechanical studies. To mimic in vivo vasculogenesis, a "scaffold-wrapping" approach has been developed to create a perfusable capillary network with a tailored structure. A cylindrical fibrin scaffold with the desired pattern and dimensions was fabricated by photolithography, thermal reflow, polydimethylsiloxane (PDMS) casting, and fibrin injection. Vasculogenesis resembling "scaffold-wrapping" was achieved by culturing human umbilical vein endothelial cells (HUVECs) on a cylindrical fibrin scaffold until all branches of the scaffold were completely wrapped by HUVECs. The scaffold was encapsulated in the collagen gel followed by plasmin treatment to form a perfusable vascular lumen. The vascular endothelial markers CD31 and VE-cadherin still expressed in the HUVECs after degradation of the fibrin scaffold. The perfusability of the vascular network was also demonstrated by injecting and imaging red fluorescent beads into the networks. This customized capillary network allowed us to control its dimensions down to the micrometer level to mimic tissue-specific microvascular properties.